2008
DOI: 10.1057/sj.2008.2
|View full text |Cite
|
Sign up to set email alerts
|

“Not the Usual Suspects”: A Study of Factors Reducing the Effectiveness of CCTV

Abstract: Previous research on the effectiveness of Closed Circuit Television (CCTV) has focused on critically assessing police and government claims that CCTV is effective in reducing crime. This paper presents a fi eld study that investigates the relationship between CCTV system design and the performance of operator tasks. We carried out structured observations and interviews with 13 managers and 38 operators at 13 CCTV control rooms. A number of failures were identifi ed, including the poor confi guration of technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…1,2 A common task for a surveillance operator in a video surveillance system is to detect critical events, which involves scanning multiple video streams to search for suspicious activities such as loitering or intrusions. 35 Studies, however, have found that human capability for this task is limited. 4,6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 A common task for a surveillance operator in a video surveillance system is to detect critical events, which involves scanning multiple video streams to search for suspicious activities such as loitering or intrusions. 35 Studies, however, have found that human capability for this task is limited. 4,6…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive survey on video surveillance system design and evaluation is beyond the scope of this article. Please refer to Keval and Sasse 5,18 and Stedmon 19 for a good discussion. Our article is also relevant to the research on video visualization.…”
Section: Introductionmentioning
confidence: 99%
“…2019 ) and, crucially, online monitoring of public spaces. Online monitoring with CCTV can be proactive or reactive (Keval and Sasse 2010 ). Proactive surveillance involves active monitoring of the CCTV array by operators in order to detect crime.…”
mentioning
confidence: 99%
“…Reactive surveillance involves operators responding to requests from other individuals within the control room or elsewhere. For example, police radio the CCTV control room to request information about a suspect, location or developing incident (Keval and Sasse 2010 ). Both proactive and reactive surveillance can aid early detection of crimes and, thus, avoid minor incidents escalating by allowing rapid and effective deployment of police resources (Levesley and Martin 2005 ; Piza et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation